“Significant Negatives”: Genre and Ethics in Alice Meynell’s Familiar Essays, 1893–1909 - Rachel O’Connell (Cahiers Victoriens et Edouardiens)
In this article I present a re-evaluation of the work of the prominent female Aesthete, Alice Meynell. While much of the critical writing on Meynell discusses her poetry, I contribute to a small body of work that focuses on her prose. I argue that Meynell’s essay collections of 1893–1909 constitute a substantive response to the ethical question of how to coexist with others without imposing upon them or being imposed upon oneself—how to live in the world without committing or suffering violence. Meynell, known for her asceticism, advocates for the negative virtues of reticence and withdrawal and recommends a stance in which one is enabled to let things—people, possessions, influence—pass through one’s hands, rather than seizing upon power. My argument can be restated as an assertion about how Meynell, best known as a poet, inhabited the landscape of prose, and what possibilities she found there. As Meynell’s imagination took on “essay-shape” she discovered an alternative to the structured world of the poem. Meynell’s use of the genre of the familiar essay constituted an exploration of the position of retreat—the refusal to impose. At the same time, Meynell’s exploration of the familiar essay’s retreating propensities inflects the genre of the familiar essay itself, emphasizing certain of its capacities over others. In this sense, Meynell’s prose writings reinterpret and repurpose the genre of the familiar essay to render it a suitable forum for confronting the ethical questions of the 1890s.